2011
DOI: 10.1152/ajpheart.00067.2011
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial C-reactive protein increases platelet adhesion under flow conditions

Abstract: While data regarding the pathogenetic role of C-reactive protein (CRP) in atherothrombosis are accumulating, it is still controversial whether local CRP secretion is of any pathobiological significance. The present study examined whether endothelial-derived CRP modulates autocrine prothrombotic activity. Endothelial cells were isolated from hearts of mice transgenic to human CRP and grown in primary cultures. Human CRP expression was confirmed in these cells compared with no expression in cultures derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The L5-induced local secretion of CRP may contribute to endothelial cell damage by means of other mechanisms, as well. Grad and colleagues [43] reported that endothelial cells expressing CRP increase platelet adhesion to human endothelial cells. Furthermore, CRP has been shown to promote atherosclerosis formation by inducing endothelial cells to produce monocyte chemoattractant protein-1 [44] and to express cell adhesion molecules [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…The L5-induced local secretion of CRP may contribute to endothelial cell damage by means of other mechanisms, as well. Grad and colleagues [43] reported that endothelial cells expressing CRP increase platelet adhesion to human endothelial cells. Furthermore, CRP has been shown to promote atherosclerosis formation by inducing endothelial cells to produce monocyte chemoattractant protein-1 [44] and to express cell adhesion molecules [45], [46].…”
Section: Discussionmentioning
confidence: 99%
“…Besides being a marker of CAD, it seems that CRP plays a causative role in CAD and ACS. It has the ability to bind to phosphocholine to recognize some pathogens and the phospholipids of damaged cells [7]; it increases platelet adhesion to endothelial cells under normal shear flow conditions [15]; it can also activate the complement system and induce synthesis of vascular cell adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1) and E-selectin and inflammatory cytokines that could promote atherosclerosis and ACS [7,16]. In this way, it seems logical that drugs that are able to lowering CRP levels, such as proinflammatory cytokines, could reduce the progression of atherosclerosis and the incidence of ACS.…”
Section: Inflammation In Atherosclerosismentioning
confidence: 99%
“…Interestingly, in experimental models, CRP promotes PMA formation and platelet adhesion to endothelial cells141516. Nevertheless, studies investigating whether circulating PMAs and CRP may mediate VTE in human thrombotic disease settings remain absent.…”
mentioning
confidence: 99%